2017
DOI: 10.1016/j.ttbdis.2017.04.011
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of a quantitative 5′ nuclease real-time polymerase chain reaction using groEL gene for Ehrlichia and Anaplasma species in rodents in Brazil

Abstract: New genotypes of Anaplasmataceae agents have been detected in wild carnivores, birds and deer in Brazil. The present work aimed to investigate the presence of Ehrlichia and Anaplasma species in rodents sampled in Brazil. Additionally, a newly designed quantitative 5' nuclease real-time multiplex PCR for Ehrlichia and Anaplasma spp. detection based on groEL gene amplification was designed, showing high specificity and sensitivity (10 groEL fragment copy/μL). Between 2000 and 2011, different rodent species [n=60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 76 publications
3
38
0
Order By: Relevance
“…Additionally, prevalences of 0.44% and 2.40% for Ehrlichia sp. and Anaplasma sp., respectively, were reported in the same study, using a newly designed multiplex quantitative real-time PCR based on the groEL gene (BENEVENUTE et al, 2017). …”
Section: Molecular Detection Of Anaplasmataceae Agents Inmentioning
confidence: 69%
See 4 more Smart Citations
“…Additionally, prevalences of 0.44% and 2.40% for Ehrlichia sp. and Anaplasma sp., respectively, were reported in the same study, using a newly designed multiplex quantitative real-time PCR based on the groEL gene (BENEVENUTE et al, 2017). …”
Section: Molecular Detection Of Anaplasmataceae Agents Inmentioning
confidence: 69%
“…in a specimen of Hylaeamys megacephalus that had been trapped in the Pantanal of the state of Mato Grosso. More recently, among 458 rodents sampled in different regions of Brazil, Benevenute et al (2017) reported prevalences of 1.09% and 1.96% for Ehrlichia sp. and Anaplasma sp., respectively, using previously described conventional PCR (cPCR) assays based on the 16S rRNA gene.…”
Section: Molecular Detection Of Anaplasmataceae Agents Inmentioning
confidence: 99%
See 3 more Smart Citations